Profesionalisme Aparatur Polisi Pamong Praja Di Kabupaten Minahasa Tenggara Dalam Pelaksanaan Tugas Penegakkan Peraturan Daerah - Lasut, Febry; Kimbal, Marthen; Waleleng, Grace (JURNAL ILMIAH SOCIETY, 2016)
This study aims to assess the professionalism of civil service police officers in the execution of duties enforcement of local regulations. From the research conducted, it can be concluded that PP atpol aparats Professionalism in Minahasa southeast in order Enforcement Regulation of Regions supported by aspects such profesionalism; Competence (in terms of recruitment and formal education), Human Resources Management System (recruitment patterns), Payroll System, Education and Training Apparatus, Reward and Punishment, Creativity, Motivation, Innovation and responsiveness. Keywords: Professionalism, Apparatus